Dissecting Naturally Arising Amino Acid Substitutions at Position L452 of SARS-CoV-2 Spike - Tan, Toong Seng; Toyoda, Mako; Ode, Hirotaka; Barabona, Godfrey; Hamana, Hiroshi; Kitamatsu, Mizuki; Kishi, Hiroyuki; Motozono, Chihiro; Iwatani, Yasumasa; Ueno, Takamasa (Journal of virology, 2022)
In a span of less than 3 years since the declaration of the coronavirus pandemic, numerous SARS-CoV-2 variants of concern have emerged all around the globe, fueling a surge in the number of cases and deaths that caused severe strain on the health care system. A major concern is whether viral evolution eventually promotes greater fitness advantages, transmissibility, and immune escape. Mutations at spike protein L452 are recurrently observed in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants of concern (VOC), including omicron lineages. It remains elusive how amino acid substitutions at L452 are selected in VOC. Here, we characterized all 19 possible mutations at this site and revealed that five mutants expressing the amino acids Q, K, H, M, and R gained greater fusogenicity and pseudovirus infectivity, whereas other mutants failed to maintain steady-state expression levels and/or pseudovirus infectivity. Moreover, the five mutants showed decreased sensitivity toward neutralization by vaccine-induced antisera and conferred escape from T cell recognition. Contrary to expectations, sequence data retrieved from the Global Initiative on Sharing All Influenza Data (GISAID) revealed that the naturally occurring L452 mutations were limited to Q, M, and R, all of which can arise from a single nucleotide change. Collectively, these findings highlight that the codon base change mutational barrier is a prerequisite for amino acid substitutions at L452, in addition to the phenotypic advantages of viral fitness and decreased sensitivity to host immunity. IMPORTANCE In a span of less than 3 years since the declaration of the coronavirus pandemic, numerous SARS-CoV-2 variants of concern have emerged all around the globe, fueling a surge in the number of cases and deaths that caused severe strain on the health care system. A major concern is whether viral evolution eventually promotes greater fitness advantages, transmissibility, and immune escape. In this study, we addressed the differential effect of amino acid substitutions at a frequent mutation site, L452 of SARS-CoV-2 spike, on viral antigenic and immunological profiles and demonstrated how the virus evolves to select one amino acid over the others to ensure better viral infectivity and immune evasion. Identifying such virus mutation signatures could be crucial for the preparedness of future interventions to control COVID-19.